PENERAPAN PENDEKATAN STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS): PEMBANGKIT LISTRIK TENAGA UAP (PLTU) SEDERHANA UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI ENERGI DAN PERUBAHANNYA SISWA KELAS IV UPT SD NEGERI 229 PINRANG - Ila Israwaty; Nur Ilmi; Aina Sumaya (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to improve learning achievement in energy material and its changes by applying the STEM approaches (Science, Technology, Engineering, and Mathematics): Simple Steam Power Plant (PLTU) for fourth grade students of UPT SD Negeri 229 Pinrang. The subjects of this study were fourth grade teachers and 12 UPT SD Negeri 229 Pinrang students for the 2020/2021 academic year consisting of 6 female students and 6 male students. Data collection techniques are observation, test and documentation. The data analysis technique was carried out through three stages, namely data condensation, data presentation and data conclusion. Based on the results of the research on the learning process in the first cycle, teacher activities obtained good qualifications (B) and student activities obtained sufficient qualifications (C), while in the second cycle, teacher activities obtained good qualifications (B) and student activities obtained good qualifications (B). Furthermore, the mastery of learning outcomes in the first cycle reached a percentage of 58.33% with an average value of 73.33, in the second cycle it increased to 83.33% with an average value of 80.33. So, it can be concluded that the increase in learning achievement in energy materials and the changes in the fourth grade students of UPT SD Negeri 229 Pinrang.Keywords: STEM approach, electric steam power plant, learning achievement